Sejarah Kesultanan Pontianak dalam Mengembangkan Pendidikan Islam di Tahun 1771-1808 M: Sejarah Kesultanan Pontianak dalam Mengembangkan Pendidikan Islam di Tahun 1771-1808 M - Suprianto, Bibi (Ngaji: Jurnal Pendidikan Islam, 2021)
This essay is written to introduce the history of Sultanate in West Kalimantan, especially to convey the history of Pontianak named (1) The purpose of the Sultanate in developing Islamic Education in 1771-1808, (2) Education curricula of the Sultanate in 1771-1808, and (3) The method of Islamic education of the Sultanate in 1771-1808. The author uses qualitative research, technically in library research, using two primary informants of data: a key master of Kadriyah palace and a key master of Jami’ Mosque of Sultan Syarief Abdurrahman Al-Qadrie. The technique used for gathering data is in-depth interview and documentation. Furthermore, the author uses accumulation, redaction, and drawing to a conclusion as the analysis data. Results indicate that 1) The goal of the Sultanate in developing Islamic Education is leading for society. 2) Curriculum used in teaching practice is Fiqh (Islamic Jurisprudence), Al-Qur’an, Hadist, and the book of al-Uum based Ahlussunnah Waljamaah. 3) Method used in Islamic education practice is lecturer method as well as in Islamic boarding schools.